Transformation of Aswaja Ideology in the Nahdlatul Ulama Pesantren (NU) - Ahmad Sunoko (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
This article describes the transformation of Aswaja's ideology through the pesantren. History that can not be avoided is teaching in pesantren which is closely related to the sustainability of Aswaja's understanding. But unfortunately the studies that have emerged have still not identified intlectual biography carefully the architects of the pesantren and have not explained the core of their teachings. Therefore, this study tries to open the curtain of knowledge about Aswaja doctrine in Islamic boarding schools. The results of this study indicate that the spread of Aswaja's ideology embraced in the NU boarding school is caused by solidarity that has deep roots and the integrity of its pesantren kiai. The ideological sources are the legacy of Wali Songo and also the works of the pesantren kiai affiliated with Aswaja's understanding. The paradigm used is that the understanding of the concept of Aswaja is flexible and moderate, awareness forms the organization, and the doctrine of Usul Fiqh is developed.